PEMBUATAN MODEL ORTOFOTO HASIL PERKAMAN DENGAN WAHANA UAV MENGGUNAKAN PERANGKAT LUNAK FOTOGRAMETRI - Virgus Ari Sondang (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
Aerial imaging using a non-metric camera that installed on Unmanned Aerial Vehicle (UAV) produce Small Format Aerial Photography (SFAP). For mapping and spatial analysis, a number of digital aerial images must be processed into an orthophoto mosaic. The aims are producing three-dimensional orthophoto mosaic model of the aerial image that acquired by using UAV and producing RMSE value that has high geometric accuracy of models. The research has been done by using aerial images for two locations in Kretek District, Bantul Regency, Special Region of Yogyakarta. The first location consists of 752 pieces of aerial image covering 375 Ha of agriculture area. The second location consists of 674 pieces of aerial image covering 1,560 Ha of coastal area. Number of GCP used for orthorectification are 4 GCP for the first location and 12 GCP for the second location. The step of researches were images election based on camera position, photo alignment, point cloud production by using image matching, GCP identification, camera optimization, texture formation, and orthophoto mosaic production. After the optimization process of placement of GCP in all aerial images, the accuracy of orthophoto models are 0,46 cm of RMSE value for the first location and 1.74 cm of RMSE value for the second location. The conclusions are orthophoto products that formed by aerial images processing with GCP have a good geometric accuracy. The RMSE values of orthophoto are smaller than GSD value. But, the form of three-dimensional objects are imperfect because the image matching process was not optimal.Keywords: foto udara format kecil, ortofoto, UAV